Analysis of Individuals’ Acceptance and Influencing Factors for Young Users of Autonomous Vehicles Using the Hybrid Choice Model - Ming Wan; Qingmei Liu; Lixin Yan; Liqun Peng; Xujin Yu; Ping Wan (Journal of Advanced Transportation)
Autonomous vehicles (AVs) are a vital direction for intelligent transportation; nevertheless, the current research is insufficient, and the aspects and mechanisms that influence individuals’ adoption of AVs require additional investigation. This study examines the acceptance of the popularity of AVs from three perspectives: personal-psychological attributes, travel characteristics attributes, and latent variables. The descriptive statistical analysis revealed that the acceptance rate of AVs was 54.6% based on 304 valid questionnaires received through online questionnaires. And the proportion of the 18∼50 group in the article reached 92.8%; thus, this study takes the young group as the object to investigate the acceptance of AVs. A quantitative analysis of each factor’s impact on the acceptability of AVs was conducted using the hybrid choice model (HCM), which was utilized to observe the link between latent variables. Results from parameter estimates demonstrate that the HCM’s fitting impact when latent factors are taken into account is superior to that when latent variables are not taken into account. When latent variables are taken into account, the associated goodness ratio coefficient rises by 0.2337 to 0.2898, which is greater than the model as a whole. The three factors with the highest impact on AV acceptability among the five latent variables were attitude toward use, sense of use gain, and perceived trust, with matching z-test values of 2.42, 2.44, and 2.12, respectively. The development and marketing of AVs by pertinent businesses and government agencies would benefit greatly from this research as a source of reference.